Optimasi Hasil Penjualan Beans Robusta Dan Arabica Pada Meranti Coffee Roastery Dengan Menerapkan Metode Simpleks Dan Software POM-QM - Hidayat, Nurul; Yonti, Kholiqul Lutfi Alfizar; Setyaningsih, Setyaningsih; Rahmani, Nur (Jurnal Ilmiah Wahana Pendidikan, 2024)
Linear programming is a computational approach utilized to address optimization issues, specifically those involving the maximization and minimization of objectives. This methodology employs methods based on linear equations and inequalities to determine the optimal solution to the problem, taking into account the given constraints. In this study, linear programming is employed to analyze the Micro, Small, and Medium Enterprises (MSMEs) operating at Meranti Coffee Roastery. MSMEs encounter challenges in accurately determining the maximum profit and optimizing the profit outcomes derived from the sale of Robusta and Arabica coffee beans during the execution of their manufacturing processes. The objective of this study is to provide a comprehensive analysis for decision-making processes aimed at optimizing production and maximizing earnings from the sale of coffee beans at Meranti Coffee Roastery. The study's findings, derived from the utilization of the simplex method, indicate that the most favorable total profit per product amounts to Rp. 225,000. The calculation procedure incorporates the aid of the POM-QM program to bolster the analysis outcomes.